Schwarzarbeit in Deutschland: bisherige Erkenntnisse und neue Befunde - Ralf K. Himmelreicher; Matthias Dütsch; Arne Baumann (Wirtschaftsdienst, 2024)
Undeclared work is a sub-sector of the shadow economy and includes the provision of services or work in circumvention of tax and social security obligations or in disregard of trade law requirements. In 2023, the Financial Control of Undeclared Work of the customs authorities determined a loss amount of around 615 million euros due to undeclared work as part of the criminal and administrative offense proceedings initiated. The number of unreported financial losses for the German state is likely to be considerably higher. Against this background, the article systematically summarises previous findings on the extent of undeclared work and provides up-to-date insight into the prevalence of undeclared work based on a 2022-23 survey.
Keywords: J46; J20; 330